2022
DOI: 10.1111/cbdd.14147
|View full text |Cite
|
Sign up to set email alerts
|

Glabridin inhibits urothelial bladder carcinoma cell growth in vitro and in vivo by inducing cell apoptosis and cell cycle arrest

Abstract: Glabridin (GLA) has a variety of biological activities and therapeutic effects in cancers. Whereas the effect of GLA on urothelial bladder carcinoma (UBC) cells and its underlying mechanisms remain unknown. The study revealed the effect of GLA on UBC and the potential mechanism of inducing cell apoptosis in vivo and in vitro. After treated with different concentrations of GLA, the cell activity decreased in a time‐ and dose‐dependent manner. The IC50 values of BIU‐87 and EJ cells at 48 h were 6.02 μg/ml (18.6 … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
4
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
5

Relationship

2
3

Authors

Journals

citations
Cited by 5 publications
(4 citation statements)
references
References 62 publications
(74 reference statements)
0
4
0
Order By: Relevance
“…After processing the cells as mentioned earlier (Yang, Bi, et al., 2023), the total protein content was assessed using a BCA reagent (PC0020, Solarbio, China). SDS‐PAGE was utilized to separate the proteins, followed by their transfer onto a PVDF membrane (Millipore, USA).…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…After processing the cells as mentioned earlier (Yang, Bi, et al., 2023), the total protein content was assessed using a BCA reagent (PC0020, Solarbio, China). SDS‐PAGE was utilized to separate the proteins, followed by their transfer onto a PVDF membrane (Millipore, USA).…”
Section: Methodsmentioning
confidence: 99%
“…After processing the cells as mentioned earlier (Yang, Bi, et al, 2023), the total protein content was assessed using a BCA reagent (PC0020, Solarbio, China). SDS-PAGE was Cell vitality = (OD of the experimental group)∕ (OD of the control group) × 100%.…”
Section: Western Blot Analysismentioning
confidence: 99%
“…The results showed that the PTX delivery system with curcumin derivatives as carrier had a strong killing effect on tumor cells rather than normal cells. Notably, our research group also found that glabridin has outstanding anti‐bladder cancer properties (IC 50 = 13.4 μM) (Yang et al, 2023), ligustilide has anti‐bladder cancer ability (IC 50 = 209.8 μM) (Yin et al, 2023), and paeonol (PAE) has certain anti‐glioma effect (IC 50 = 527.29 μM) (Hao et al, 2023).…”
Section: Introductionmentioning
confidence: 95%
“…Glabridin, a prenylated isoflavone found in the roots of G. glabra L. (European licorice, Fabaceae), has a wide variety of biological effects, including antioxidant, anti-inflammatory, anti-atherogenic, regulation of energy metabolism, estrogenic, neuroprotective, anti-osteoporotic, and skin-whitening effects [ 24 ]. Glabridin has many biological functions and therapeutic benefits in cancer treatment [ 25 ], including anti-inflammatory and antioxidant properties. The pharmacological effects of Glabridin are numerous and include the prevention of Staphylococcus, Candida , and other bacterial infections, the treatment of metabolic abnormalities to reduce obesity, diabetes, and cardiovascular disease, the protection of nervous system function, the prevention of cancer, the treatment of inflammation, the treatment of osteoporosis, etc.…”
Section: Ligand Selection and Their Earlier Effectiveness Of The Stud...mentioning
confidence: 99%